Seronegative Granulomatous Myositis With Bulbar Weakness and Reversible Cardiomyopathy: A Case Report - Balachandran R. Vaidyanathan; Muhamed Abubacker; John Ponugupati (Clinical Case Reports, 2026)
ABSTRACT A 64‐year‐old woman presented with seronegative idiopathic granulomatous myositis, featuring severe bulbar weakness, reversible cardiomyopathy (ejection fraction 20%–25%), hepatic injury, and acute kidney injury. Muscle biopsy confirmed granulomatous inflammation. Treatment with corticosteroids and intravenous immunoglobulin resulted in multi‐organ recovery, highlighting the importance of early immunosuppressive therapy.